Corporate insolvency laws in abandoned housing projects: Issues and prospects - Md Dahlan, Nuarrual Hilal (Universiti Utara Malaysia Press, 2014)
This book discusses the provisions and legal principles under the Insolvency Law in Malaysia in face of the issue of abandoned housing projects and its rehabilitation. Apart from the Malaysian Insolvency Law, this book also analyses comparatively between the insolvency legal provisions and legal principles under the United Kingdom and Singapore Insolvency Laws. The approach of this book is by way of legal analyses over the relevant insolvency legal provisions in Malaysia, the United Kingdom and the Republic of Singapore.The discussion is further enriched and collaborated by the case studies conducted over several abandoned housing projects in Malaysia that have been subject to the insolvency administration. In addition, the author also provides relevant official statistics and reports of abandoned housing projects and numerous examples of abandoned housing project cases illustrating the diverse problems, complications, issues and grievances.The outcome and proposals of this book will be beneficial to the legal practitioners, judicial and legal services, insolvency practitioners, housing developers, financial institutions, contractors, housing consultants, technical agencies, land and state authorities, purchasers of units in abandoned housing projects, consumers’ associations, relevant private and government agencies and Federal and States Ministries, students and policy makers in the insolvency legal administration in Malaysia, particularly for those who are directly involved in abandoned housing projects and its rehabilitation in Malaysia.